Emergency department observation implementation guide - Kyle W. Trecartin; Richard E. Wolfe (Journal of the American College of Emergency Physicians Open)
Abstract Emergency department (ED) crowding poses significant operational challenges to hospitals. One strategy to address these issues is the implementation of an ED observation (EDO) unit. EDO involves placing patients in observation status after their initial evaluation, allowing for continued assessment, treatment, and the determination of a safe disposition. This paper provides a comprehensive guide for ED leaders on the implementation of ED observation in their departments. It includes a checklist summarizing key implementation points, operational and financial considerations, staffing and location planning, patient selection, clinical care protocols, documentation and communication processes, securing buy‐in from stakeholders, and outcome measurement. The guide also highlights the updated billing codes based on the 2023 updated Current Procedural Terminology (CPT) guidelines. Successful implementation of an EDO program has shown benefits such as improved patient flow, enhanced revenue generation, reduced costs, and comparable clinical outcomes. This guide aims to equip ED leaders with the necessary knowledge and tools to implement and manage an effective ED observation program in their departments, ultimately improving the overall efficiency of emergency care delivery.